PENILAIAN PENGGUNAAN PERANCAH BAGI KESELAMATAN DAN KESEHATAN KERJA - Brian Mamahit; Widodo Kushartomo; Andy Prabowo (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Multi-storey building construction work requires a good scaffolding to support people, materials and tools, as well as structures that are in accordance with the plan. The purpose of this study is to determine the extent of implementation of occupational health and safety manajement systems in construction projects. Along with the development of science and technology, the scaffolding tools produced are increasingly complex. The more complex the device used, the larger the size  potential hazard that may be and the greater the work accident caused if the handling and control is not carried out as well as possible. This shows that occupational safety and health issues cannot be separated from construction work activities as a whole. The method used in this study uses an observational and quantitative investigation method. This method tends to give more descriptive results. After data is collected, it is identified and analyzed. The analysis shows that the implementation of the framework design is  Thamrin Nine project, Central Jakarta, shows that it must be further improved when viewed from the applicable standards for occupational safety and health. Abstrak Dalam setiap pekerjaan konstruksi gedung bertingkat, selalu diperlukan perancah (scaffolding) yang berfungsi sebagai penopang bekisting maupun platform pekerja/tukang. Karena frekuensi penggunaan yang sangat tinggi, maka dilakukan pengamatan pada satu proyek konstruksi guna mengetahui sejauh mana efektifitas penggunaan perancah dalam mendukung manajemen kesehatan dan keselamatan kerja (K3). Pengamatan yang dilakukan menjadi metode kuantitatif untuk melakukan penelitian sederhana selama melakukan kegiatan magang dari program Merdeka Belajar Kampus Merdeka (MBKM) pada proyek gedung X di kawasan Jakarta Pusat. Pada proyek magang tersebut, diperoleh data penggunaan perancah untuk berbagai keperluan penunjang pekerjaan konstruksi yang menggunakan beberapa tipe perancah. Dari hasil pengamatan, diperoleh evaluasi sejauh mana penggunaan perancah pada proyek magang mendukung aspek K3 pada proyek konstruksi. Hasil evaluasi menunjukan perlu adanya peningkatan kualitas penggunaan perancah pada proyek magang untuk memenuhi aspek K3 dan meminimalisir kecelakaan kerja.